Possibilities for wind operators participating in markets for frequency support services - Ivanova, Anzhelika; Mateska, Aleksandra Krkoleva; Krstevski, Petar; Dominguez Garcia, Jose Luis (IEEE, 2017)
The imbalance between consumption and demand, caused by the integration of intermittent renewable energy sources (ReS), increases the need of Ancillary Services (AS) for frequency support (FS). This imbalance is still regulated with the help of conventional generation, by procuring reserves for frequency support. However, as the aim is to increase the share of RES in electricity generation, they would have to be able to provide reserves for FS, as well. This paper analyses the possibilities for wind power generation to be included in the provision of these reserves, in particular the manual frequency restoration reserves and the replacement reserves markets. The analysis is done by solving a Linear Programming (LP) optimization problem that investigates the optimal amounts of energy a wind power producer should sell on the day ahead and on the balancing market in order to maximize its income.
Keywords: ancillary services, balancing market, frequency control provision, wind power